EXPORT SPECIALIZATION OF SOUTH EAST EUROPEAN COUNTRIES IN THEIR TRADE WITH THE EUROPEAN UNION - Muamer Halilbašić; Snježana Brkić (Economic Review)
Evolving of trade specialization is usually a long-lasting process resulting from deep structural changes of an economy. In some cases external stimuli such as broader market that resulted from trade liberalization could contribute to a rapid changing of a country’s trade pattern. Although trade specialization in its broader sense includes both supply (export) and demand (import) specialization, export patterns of countries and their changes are given most focus in international trade research.The paper investigates export specialization of South East European countries (SEECs) in their trade with the European Union (EU) before and after starting trade liberalization introduced by the Stabilization and Association Agreements (SAA). Comparing 2003 and 2014, the paper aims to verify whether the export pattern of six SEECs (Albania, Bosnia and Herzegovina, Croatia, FYR Macedonia, Montenegro and Serbia) has moved toward the EU demand as in the case of advanced transition countries that joined the EU in 2004. Following empirical trade literature, the research employs several different indicators: indicator of export composition and revealed comparative advantage (Balassa RCA index), indicator of dynamics of trade specialization (Michaely index, the Lorenz curve, Gini coefficient), indicator of export diversification (Herfindahl-Hirschman index of sectoral export concentration), and export quality indicator (export product classification by technology level). As the reference for calculating the indices and plotting the Lorenz curve, EU27 total imports were used. The research results indicate a slight despecialization in most analysed countries. Their export structure, although significantly changed, remains highly concentrated and dominated by primary products, resource based products, and low-technology intensive products. Despite positive trends in terms of slight movement of export structure toward the EU demand, especially in cases of Croatia and Serbia, large inconsistency with the needs of the EU market still exists, indicating that SEECs have a long way to catch up with the EU.